2008
DOI: 10.1016/j.jmb.2008.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipid Composition on the Topography of Membrane-Associated Hydrophobic Helices: Stabilization of Transmembrane Topography by Anionic Lipids

Abstract: To investigate the effect of lipid structure upon the membrane topography of hydrophobic helices, the behavior of hydrophobic peptides was studied in model membrane vesicles. To define topography, fluorescence and fluorescence quenching methods were used to determine the location of a Trp at the center of the hydrophobic sequence. For peptides with cationic residues flanking the hydrophobic sequence, the stability of the transmembrane (TM) configuration (relative to a membrane-bound non-TM state) increased as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 62 publications
5
34
1
Order By: Relevance
“…In addition, there was a correlation between the extent of transverse shift induced by hydrophilic residues and the previously reported activating effects of these residues upon transformation due to Erb b2 expression 9. Other experiments indicated that anionic lipid could suppress transverse shifts when the juxtamembrane residues flanking the TM sequence were cationic, but not when they had no net charge 21. How such transverse movements and their regulation might influence Erb b2 function is discussed.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…In addition, there was a correlation between the extent of transverse shift induced by hydrophilic residues and the previously reported activating effects of these residues upon transformation due to Erb b2 expression 9. Other experiments indicated that anionic lipid could suppress transverse shifts when the juxtamembrane residues flanking the TM sequence were cationic, but not when they had no net charge 21. How such transverse movements and their regulation might influence Erb b2 function is discussed.…”
Section: Introductionmentioning
confidence: 58%
“…We previously found that anionic lipids strongly stabilize the formation of a TM topography when a hydrophobic sequence is flanked by cationic JM residues 21, 30. This appears to involve Coulombic electrostatic interactions between the cationic JM residues and anionic lipids 21.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Low PG and CL contents initially caused an increased GlpF activity, whereas we observed a decreased GlpF activity at higher negative charge levels. Stabilizing effects of small amounts of anionic lipids on the configuration of TM helices that are flanked by cationic residues were previously described for both PG and PS (50). This effect on GlpF activity, however, seems to be lipid-headgroup specific, as PS did not increase the GlpF activity.…”
Section: Discussionmentioning
confidence: 75%